Overactivated BNIP3-dependent mitophagy as a driver of immobilization-induced muscle atrophy: therapeutic mechanism of extracorporeal shock wave in improving myogenic contracture - F Wang; CX Zhou; T Zhou; LY Ni; QB Zhang; Y Zhou (European Cells & Materials)
Purpose: The purpose of this study is to investigate the role of Bcl2/adenovirus E1B 19kDa protein-interacting protein 3 (BNIP3)-dependent mitophagy in immobilization-induced muscle atrophy and explore the potential mechanism responsible for ameliorating myogenic contracture through extracorporeal shock wave (ESW). Methods: A rat model of myogenic contracture was developed by immobilizing the knee joint, and muscle atrophy and mitophagy were assessed in vivo. Subsequently, we verified the role of mitophagy in muscle atrophy through in vitro. Finally, we examined the potential therapeutic effects of ESW on immobilization-induced muscle atrophy and myogenic contracture, and assessed the role of mitophagy in the observed alleviation of symptoms. Results: Immobilization had significant time-dependent effects on muscle atrophy. It triggered the production of excessive reactive oxygen species (ROS) and subsequently overactivated hypoxia-inducible factor (HIF)-1α/BNIP3-dependent mitophagy in the rectus femoris. Excessive mitophagy resulted in the elimination of mitochondria, leading to a shortage of adenosine triphosphate (ATP). As ATP homeostasis was crucial for maintaining muscle mass, the shortage of ATP resulted in reduced muscle mass and cross-sectional area, as well as slow-to-fast myofiber type transition. These findings were corroborated by an in vitro study that pretreatment with BNIP3 small interfering RNA (siRNA) reduced the level of BNIP3-dependent mitophagy and partially counteracted the inhibition of myogenic differentiation caused by high levels of ROS. Notably, ESW was found to suppress ROS generation, inhibit overactivated HIF-1α/BNIP3-dependent mitophagy, and preserve mitochondrial quantity in the rectus femoris. Conclusions: Our findings suggest that ESW can inhibit overactivated BNIP3-dependent mitophagy in immobilized muscles, which could be one of the potential therapeutic mechanisms attenuating immobilization-induced muscle atrophy and further improving myogenic contracture.